Polygamy Permit: Perspective of Mashlahah Mursalah on Wahbah Al-Zuhaili Thought - Haekal, Mohammad Rifki; Hannase, Mulawarman (UI Scholars Hub, 2025)
Polygamy in Islamic tenets is a difficult thing to do. It is required to be able to act fairly in fulfilling all the rights of his wives. Meanwhile, polygamy, which is allowed by Islam, is also limited to a maximum of four wives at a time. Therefore, many countries then provide a regulation in the form of a polygamy permit to create mashlahah in society, especially in the household. The regulation states that a husband who wants to have polygamy must obtain permission from the Court. In the scientific treasures of fiqh, creating benefit is the goal of the existence of law. One form of legal istinbath method for producing the benefit is mashlahah mursalah. Imam Malik first introduced this method. However, many contemporary scholars at this time also contributed to their scientific contributions in discussing this method, one being Wahbah Al-Zuhaili. The author uses normative research, which emphasizes the source of library data (library research), passed through the stages of collecting data and information containing various library materials such as books, journals, articles, encyclopedias, and others. The research approach in data management used by the author is descriptive-analytical. That is, by explaining the problem's form in detail and then analyzing it deductively.